2003
DOI: 10.1034/j.1399-0039.2003.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Total loss of MHC class I in colorectal tumors can be explained by two molecular pathways: β2‐microglobulin inactivation in MSI‐positive tumors and LMP7/TAP2 downregulation in MSI‐negative tumors

Abstract: The mechanisms that lead to loss of MHC class I expression in different types of tumors are not yet fully known. Accordingly, we studied colorectal carcinomas to elucidate the specific mechanisms of evasion of the T-cell immune response. We selected tumors with total loss of MHC class I expression and studied 124 colorectal carcinomas with immunohistochemical staining and anti-HLA monoclonal antibodies (mAb). Fourteen of 124 (11%) tumors exhibited a phenotype with HLA class I total loss. Microsatellite instabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 34 publications
9
107
0
1
Order By: Relevance
“…The downregulation of MHC expression, including the TAP1 and LMP2 genes, is one of the biological mechanisms tumor cells use to evade host immunosurveillance (Singal et al, 1996;Dovhey et al, 2000;Cabrera et al, 2003). Recently, the incidence of IFN-g unresponsiveness in human tumors was examined in several cancers, and revealed that approximately 33% of each group exhibited a reduction in IFN-g sensitivity (Kaplan et al, 1998).…”
Section: Impaired Jak1 Activation In Uterine Leiomyosarcoma Cells T Hmentioning
confidence: 99%
See 2 more Smart Citations
“…The downregulation of MHC expression, including the TAP1 and LMP2 genes, is one of the biological mechanisms tumor cells use to evade host immunosurveillance (Singal et al, 1996;Dovhey et al, 2000;Cabrera et al, 2003). Recently, the incidence of IFN-g unresponsiveness in human tumors was examined in several cancers, and revealed that approximately 33% of each group exhibited a reduction in IFN-g sensitivity (Kaplan et al, 1998).…”
Section: Impaired Jak1 Activation In Uterine Leiomyosarcoma Cells T Hmentioning
confidence: 99%
“…Total RNA was prepared from 5 Â 10 6 cells using TRIzol reagent according to the manufacturer's protocol (Invitrogen Co., CA, USA). The RNA was reverse-transcribed with the Superscript II enzyme (Invitrogen Co., CA, USA), the single-strand cDNA was used to amplify TAP1, LMP2, b2-m and b-actin transcripts using PCR analysis with the appropriate primer sets following a program of 35 cycles of 941C for 30 s, 601C for 30 s and 721C for 1.5 min with an additional 5 min for the extention of transcripts (Cabrera et al, 2003;Miyagi et al, 2003).…”
Section: Impaired Jak1 Activation In Uterine Leiomyosarcoma Cells T Hmentioning
confidence: 99%
See 1 more Smart Citation
“…No attempt was made to score cytoplasmic staining with HC10, as it has been observed that the antibody defines free HLA class I heavy chain and thus may show a positive reaction in the cytoplasm in tumors with W6/32 negativity and no surface MHC class I expression. 14 In the case of b 2 -microglobulin staining, tumors were categorised as either b 2 -m negative (complete absence of tumor cell staining) or b 2 -m positive. Where discrepancies arose between the staining of cores from the same tumor, an average of the evaluable cores was taken, with confirmation by 2 observers (Z.M.…”
Section: Evaluation Of Tma Immunostainingmentioning
confidence: 99%
“…For example, immune evasion mechanisms such as impairment or loss of the human leukocyte antigen class I-mediated antigen presentation (Bicknell et al, 1996;Cabrera et al, 2003;Kloor et al, 2005) or the expression of Fas ligand (Okada et al, 2000;Michael-Robinson et al, 2003) are frequent in MSI-H CRCs.…”
mentioning
confidence: 99%